PRODUKTIVITAS PADI SAWAH PADA KEPADATAN POPULASI BERBEDA - Sumardi Sumardi (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2010)
[THE PRODUCTIVITY OF LOWLAND RICE UNDER DIFFERENT POPULATION DENSITIES]. Population density will determine the crop productivity on either individual plant basis or area basis. Objective of this study was to evaluate the productivity  of lowland rice at different population densities.  Rice variety IR-64 was planted on 13.2 m x 10 m plot at four population densities (16, 25, 49 and 100 plant m-2)  in a completely randomized design with three replications. Observations were made on the yield components on individual plant basis and grain yield per area. Results indicated that tiller number, number of productive tiller, number of spikelet per panicle, number of fertile spikelet, and grain yield per hill were reduced  as the population density was increased.  On contrary, grain yield per 100 m2 was increased linearly in accordance to the increment of population density, where 47.57 kg grain per 100 m2 produced at the density of 16 plant m-2 and 86.53 kg was produced at the density of 100 plant m-2.